Determinants of Aging Population in East Asia: A Panel Data Analysis 2005-2024 - Emmiya Nalsa Lisa Br Brahmana; Rizky Putri Rismawati; Dwi Kurnia Wati; Berliana Claristaningrum; Nufuzia Fadriani; Fera Febriana Sritutur (Universitas Muhammadiyah Purwokerto, 2026)
This study aims to analyze the determinants of aging population with GDP growth as a control variable in the East Asian region, covering China, Hong Kong, Japan, South Korea, and Mongolia, with the exclusion of North Korea due to data availability limitations. The study uses secondary data in the form of panel data for the period 2005-2024 sourced from the World Bank and processed using the E-Views application. The results show that fertility rate has a negative and significant effect on aging population, while life expectancy and female labor force participation rate (FLFP) each have a positive and significant effect on aging population in the East Asian region during the 2005-2024 period. Meanwhile, GDP growth as a control variable shows no significant effect, indicating that population aging is more influenced by long-term structural demographic factors than by short-term economic dynamics